PENGARUH GANDA KOMODITI UBI KAYU DALAM PEREKONOMIAN SULAWESI TENGAH - M.R. Yantu; Yulianti Kalaba; Sisfahyuni Sisfahyuni (Universitas Tadulako, 2013)
The aim of this study were (i) to analyze multiplier effect of cassava commodity in economy of Central Sulawesi, and (ii) to analyze trend of the multiplier effect during the last decade. Methods of analyses used were analyses of multiplier effect of Tiebout economic base model, and analyses of trend. Data used were secondary data of time series 2000 – 2011, i.e. Data of GDRP of Central Sulawesi by sector, area size, volume of production, and prices of all kinds of cassava. The result of analyses showed that coefficient of multiplier effect of the cassava commodity in economy of Central Sulawesi was more than one. It indicated that investment of developing for the commodity in Central Sulawesi is feasible. In the long-run, the coefficient tends to increase. It indicates that continuously investment for the commodity to increase the performance of economy of Central Sulawesi is feasible. Key Words : Cassava, economy of Central Sulawesi, multiplier effect.